﻿Synthesis and antioxidant properties of new (2,4- and 3,4-dimethoxyphenyl)-1,2,4-triazoles - Dmitro V. Dovbnya; Andriy H. Kaplaushenko; Yuliia S. Frolova; Evheniy S. Pruglo (Pensoft Publishers, 2022)
The purpose of the work is to develop preparative methods for the synthesis of ((5-(2,4- and 3,4-dimethoxyphenyl)-3H-1,2,4-triazole-3-yl)thio)aceto(propano-, butano-, benzo)nitriles, to investigate the reaction of acid hydrolysis, to receive the physical-chemical properties of the synthesized compounds, and to study antioxidant activity of new compounds. Preparative methods for the synthesis of (5-(2,4- and 3,4-dimethoxyphenyl)-3H-1,2,4-triazole-3-yl)thio)aceto(propano-, butano-, benzo)nitriles have been developed for which studied the reaction of acid hydrolysis, resulting in the production of carboxylic acids. The structure of the obtained substances was confirmed by modern physical-chemical methods. The antioxidant activity of the synthesized compounds was evaluated in vitro by the method of the non-enzymatic initiation of BOD with salts of iron (II).